PERAN SOLUBLE GROWTH STIMULATION GENE-2 (sST2) PLASMA DARAH SEBAGAI FAKTOR PROGNOSTIK PREEKLAMSIA BERAT - Pratama, Yonathan Siswo; Maharani, Laksmi (Essential: Essence of Scientific Medical Journal, 2019)
This article is aimed to know the role of soluble growth stimulation gene-2 (sST2) as a prognostic factor in patients with severe preeclamsia. A search was conducted on Pubmed, GoogleScholar and ScienceDirect based on selected clinical question. The articles selection was based on inclution and exclution criteria. Three articles were critically appraised for its validity, importance and applicability. All three choosen articles state that higher sST2 plasma is correlated with overall survival patients with severe preeclamsia. SST2 level may serve as a prognostic factor regarding overall survival in patients with severe preeclamsia.